Co-Application of Porous Polysulfide Pellets with Acidithiobacillus thiooxidans Improves Sulfate Availability in Soil - Valle, Stella F.; Giroto, Amanda S.; Klaic, Rodrigo; Bevilaqua, Denise [UNESP]; Ribeiro, Caue (Springer Nature, 2022)
Sulfur (S) fertilization is necessary to overcome the low availability of this essential nutrient in agricultural soils. Although elemental sulfur (S8) pellets are often used, they tend to be poorly effective due to their low oxidation rate to sulfate, the form assimilated by plants. Here we designed highly porous polysulfide pellets (PolyS-porous) as S fertilizers with higher surface area for oxidation, aiming to improve sulfate delivery. A porosity of nearly 50% was achieved via inverse vulcanization of soybean oil and S8 in the presence of a salt porogen. A culture medium test with S-oxidizing bacterium Acidithiobacillus thiooxidans revealed PolyS-porous had a faster initial oxidation than S8-pellet, reaching respectively 57% and 20% at the end of 10 days. Sulfate released from PolyS-porous in soil was 3 times higher than from S8-pellet in 30 days, and PolyS-porous co-application with A. thiooxidans achieved twice as much. Overall, the results from this study demonstrated the potential of porous polysulfide pellets as sulfur fertilizers with improved efficiency, especially when combined with A. thiooxidans. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Acidithiobacillus thiooxidans; Fertilizer; Oxidation; Polysulfide; Sulfur